Annual Plan 1986-87 Government of India Planning Commission - Planning Commission (Planning Commission, 1986)
The Annual Plan for 1986-87 has been formulated within the framework of the objectives, policies and programmes indicated in the Seventh Five Year Plan and takes into account the performance of the economy in 1985-86. While seeking to promote balanced growth, it lays emphasis on the implementation of area-specific and beneficiary-oriented antipoverty programmes in order to generate additional employment and incomes for the weaker sections of the society.
Government of India, Planning Commission